Dampak Pemindahan IKN Nusantara dan Tantangannya Terhadap Pembangunan Perekonomian Lokal - Oktavia, Elisa Wulan; Istamala, Nadia; Adityanto, Adityanto; Sagena, Uni W; Masjaya, Masjaya; Rahman, Ishaq; Irmawati, Irmawati (Program Pascasarjana STIE Amkop Makassar, 2024)
This study aims to evaluate the potential effects of relocating the national capital on the local economy, design strategies to maximize economic and social benefits, and identify challenges. The research methods applied include literature and policy analysis, with a qualitative approach and descriptive analysis of available data. The results show that relocating the national capital has a significant impact on the local economy. First, the construction of new infrastructure such as roads, bridges, and other public facilities has increased investment and economic growth in the surrounding area. Second, the presence of a new government has increased economic activity through demand for administrative services, which positively affects sectors such as property, hospitality, and transportation. However, relocating the capital also presents challenges such as increasing property prices that can lead to gentrification, as well as social and demographic changes that require careful spatial planning and effective social impact management. Suggested mitigation efforts include sustainable spatial planning, social infrastructure development, local economic empowerment, and continuous monitoring of the impacts that occur. Thus, relocating the national capital has the potential to improve the local economy, but this can only be achieved through careful management and appropriate mitigation strategies.